2022
DOI: 10.1155/2022/1151676
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Emotional Cognitive Expression in Lacquer Colors Based on Prior Knowledge

Abstract: Since lacquer painting first appeared in the world of art, research into it has grown steadily. People have developed a keen interest in modern lacquer painting as a result of the extensive study of lacquer culture in both domestic and international academic circles. Many artists and art enthusiasts have contributed significantly to the study and research of lacquer painting and have made helpful attempts at modern lacquer painting. But it is challenging to describe the emotion that a lacquer painting’s color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Wei [5] discusses the decision-making framework for emotional and cognitive learning based on the emotional and mental evaluation theory. The focus is on the relationship between lacquer paintings and emotions, which has yet to be explored due to the limited research materials and documents.…”
Section: Related Workmentioning
confidence: 99%
“…Wei [5] discusses the decision-making framework for emotional and cognitive learning based on the emotional and mental evaluation theory. The focus is on the relationship between lacquer paintings and emotions, which has yet to be explored due to the limited research materials and documents.…”
Section: Related Workmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%